Hematological changes of Anemia`s in Horses of Equestrian club in Baghdad: Faisal G.Habasha1, Walla Mohamaad Abaas and TahaYassinGhani - Habasha, Faisal G. (The Iraqi Journal of Veterinary Medicine, 2012)
This study was conducted to know thehematological changes of anemia in horsesat equestrian club in Baghdad. Blood samples were collected from 151 horses of both sexes(74 male and 77 female) and different agesrandomly. The study includedred blood cells count, white blood cells, hemoglobin, packed cell volume and differential blood smears, togetherwith erythrocyte sedimentation rate readings. The study showed increased white blood cells count mainly neutrophilwith decreased hemoglobinand red blood cell countin addition to erythrocyte sedimentation rate.The blood smears showeddifferent changes of red blood cell.